2020
DOI: 10.1038/s41598-019-56981-z
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of The Human Ape1 Interactome Defines Novel Cancers Signatures

Abstract: APE1 is essential in cancer cells due to its central role in the Base Excision Repair pathway of DNA lesions and in the transcriptional regulation of genes involved in tumor progression/chemoresistance. Indeed, APE1 overexpression correlates with chemoresistance in more aggressive cancers, and APE1 protein-protein interactions (PPIs) specifically modulate different protein functions in cancer cells. Although important, a detailed investigation on the nature and function of protein interactors regulating APE1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 118 publications
1
27
0
Order By: Relevance
“…In addition, a large number of DNA BER proteins have been investigated as a potential biomarker and therapeutic target [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a large number of DNA BER proteins have been investigated as a potential biomarker and therapeutic target [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…After staining with colloidal Coomassie blue, whole gel lanes were cut into 12 slices, minced and washed with water. Corresponding proteins were separately in-gel reduced, S -alkylated with iodoacetamide and digested with trypsin, as previously reported 59 . Individual protein digests were then analyzed with a nanoLC-ESI-Q-Orbitrap-MS/MS platform consisting of an UltiMate 3000 HPLC RSLC nano system (Thermo Fisher Scientific) coupled to a Q-ExactivePlus mass spectrometer through a Nanoflex ion source (Thermo Fisher Scientific) 59 .…”
Section: Methodsmentioning
confidence: 99%
“…Corresponding proteins were separately in-gel reduced, S -alkylated with iodoacetamide and digested with trypsin, as previously reported 59 . Individual protein digests were then analyzed with a nanoLC-ESI-Q-Orbitrap-MS/MS platform consisting of an UltiMate 3000 HPLC RSLC nano system (Thermo Fisher Scientific) coupled to a Q-ExactivePlus mass spectrometer through a Nanoflex ion source (Thermo Fisher Scientific) 59 . Peptides were loaded on an Acclaim PepMap RSLC C18 column (150 mm × 75 μm ID, 2 μm particles, 100 Å pore size) (Thermo Fisher Scientific), and eluted with a gradient of solvent B (19.92/80/0.08 v/v/v water/acetonitrile/formic acid) in solvent A (99.9/0.1 v/v water/formic acid), at a flow rate of 300 nl/min 59 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA-(apurinic or apyrimidinic site) lyase (APEX1) functions as the AP endonuclease in the BER pathway. With the same co-IP strategy, an APEX1 protein‒protein interaction network was built, which revealed that the signature of APEX1 interactome is associated with poor prognosis in several types of cancers ( Ayyildiz et al, 2020 ).…”
Section: Application Of Interactome Determination In the Investigatmentioning
confidence: 99%